2011
DOI: 10.3402/fnr.v55i0.7253
|View full text |Cite
|
Sign up to set email alerts
|

Lactase persistence and milk consumption are associated with body height in Swedish preadolescents and adolescents

Abstract: BackgroundBody height is a classic polygenic trait. About 80%–90% of height is inherited and 10%–20% owed to environmental factors, of which the most important ones are nutrition and diseases in preadolescents and adolescents.ObjectiveThe aim of this study was to explore potential relations between the LCT (lactase) C>T-13910 polymorphism, milk consumption, and body height in a sample of Swedish preadolescents and adolescents.DesignIn a cross-sectional study, using a random sample of preadolescents and adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…After accessing the full texts, 16 records were included 13 , 19 , 30 , 36 , 37 , 45–53 . One additional record 16 was identified in the reference lists of the included records, totalling 17 records (Supplementary Figure 2, available as Supplementary data at IJE online).…”
Section: Resultsmentioning
confidence: 99%
“…After accessing the full texts, 16 records were included 13 , 19 , 30 , 36 , 37 , 45–53 . One additional record 16 was identified in the reference lists of the included records, totalling 17 records (Supplementary Figure 2, available as Supplementary data at IJE online).…”
Section: Resultsmentioning
confidence: 99%
“…The highest milk intake was in Finland and Sweden, where the difference in milk intake between lactase TT/TC-persistent individuals and lactase CC-nonpersistent individuals was largest. Also, there seems to be a similar gradient in milk intake because individuals from northern Europe (22,23) report higher milk intakes than do individuals from southern Europe (25), and milk intake in northern Europe seems to be consistently higher in lactase-persistent individuals than in lactase-nonpersistent individuals. There is a north-south gradient of lactase persistence in Europe, with prevalences ranging from 80% in northern Europe to 5-10% in southern Europe (26,27).…”
Section: Strengths and Limitationsmentioning
confidence: 94%
“…Some studies have confirmed a positive association between the LP allele and BMI (Almon et al, 2011;Corella et al, 2011;Kettunen et al, 2010). It can be explained by differences between LNP and LP, in terms of gut microbiota which may influence the caloric extraction of ingested food (Armougom et al, 2009;Suchy et al, 2010) or hormonal/peptide/fatty-acid constituents in milk having biological effects on consumers, which may potentially exert an effect on body composition (Adebamowo et al, 2008;Berkey et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the research has been based on small research groups ( Khabarova et al, 2009 ; Madry et al, 2010 ), mainly among children and teenagers ( Almon et al, 2011 ; Madry et al, 2010 ), elderly people ( Corella et al, 2011 ; Smith et al, 2009 ), or the sick ( Travis et al, 2013 ). There is a lack of population-based research concerning healthy middle-aged people of both sexes, using exact anthropometric measurements estimating the amount of adipose tissue and non-fat mass.…”
Section: Introductionmentioning
confidence: 99%